An Analysis of Interrelationships between Antecedents of Customer Loyalty: Context of Sri Lankan Veterinary Healthcare Services (Singaporean Journal of Business Economics and Management, 2018)
This study intended to investigate antecedents of customer loyalty and their interrelationships in Sri Lankan veterinary healthcare context. At the end of the critical reviewing process of extant literature, researchers developed a questionnaire. In order to obtain necessary data, researchers administered a questionnaire with five constructs. Namely, Corporate image, perceived service quality, perceived value, customer satisfaction and customer loyalty. All required responses were obtained by seven point Likert Scale. A total of 150 valid samples collected through convenience sampling technique at the Immunization Unit of the Veterinary Teaching Hospital. For the data analysis of this exploratory study, researchers decided to adopt variance-based Structural Equation Modeling by Partial Least Square (PLS-SEM). The data analysis performed in two stages. Firstly, measurement model analyzed for validity and reliability. Later, structural model analyzed for derive direct and indirect relationships. All hypothesized relationships except between perceived value and customer loyalty are significantly positive. However, customer satisfaction plays a role of full mediation between perceived value and customer loyalty. Perceived service quality plays partial mediation between corporate image and perceived value. Furthermore, perceived value plays partial mediation between perceived service quality and customer satisfaction. Finally, researchers conclude corporate image, perceived service quality, perceived value and customer satisfactions are antecedents for customer loyalty and they impose direct, and highly complex full, partial and multiple mediation effect on customer loyalty.